1990
DOI: 10.1093/jnci/82.9.772
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Production of Nitrogen Oxides in Response to Interferon   in Combination With Tumor Necrosis Factor, Interleukin-1, or Endotoxin

Abstract: Clinical studies using biological response modifiers in cancer therapy have shown that the major dose-limiting toxic effects are hypotension and diffuse microvascular leakage. The cause and pathophysiology of this hypotension remains unknown. Previous experiments have demonstrated that a number of cell types, including endothelial cells, neutrophils, and macrophages, can secrete a potent hypotensive agent--endothelium-derived relaxing factor, which has recently been identified as nitric oxide. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
157
1
4

Year Published

1991
1991
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(171 citation statements)
references
References 0 publications
9
157
1
4
Order By: Relevance
“…And it was shown very recently that the 1L-1/~-induced inhibition of insulin secretion is also reversible by adding NMA [14,15]. Islets contain a dense capillary network [I 6] and endothelial cells have been shown to be inducible for generating large amounts of nitric oxide by cytokines, eSl~-cially IL-1]~ in synergny with TNF~ and/or IFN-7 [17][18][19][20]. Indeed, we find that the slightly enhanced lysis seen in the presence of both IL-I~ and TNF was also completely blocked by NMA.…”
Section: Discussionmentioning
confidence: 99%
“…And it was shown very recently that the 1L-1/~-induced inhibition of insulin secretion is also reversible by adding NMA [14,15]. Islets contain a dense capillary network [I 6] and endothelial cells have been shown to be inducible for generating large amounts of nitric oxide by cytokines, eSl~-cially IL-1]~ in synergny with TNF~ and/or IFN-7 [17][18][19][20]. Indeed, we find that the slightly enhanced lysis seen in the presence of both IL-I~ and TNF was also completely blocked by NMA.…”
Section: Discussionmentioning
confidence: 99%
“…Inducible NOS (iNOS) is calcium-independent and produces large amounts of NO which may mediate cGMP-independent cytotoxicity against microorganisms and tumor cells (Stuehr and Nathan, 1989). iNOS is found in a variety of cells such as macrophages (Marletta et al, 1988), endothelial cells (Kilbourn and Belloni, 1990) and glial cells . While all three types of NOS may be expressed in astrocytomas (Cobbs et al, 1995), expression of iNOS was only observed in high-grade tumors and mainly restricted to endothelial cells within the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Like LPS, TNF also induces the calcium-independent isoform of NOS in vitro (Drapier et al, 1988;Kilbourn & Belloni, 1990). Systemic administration of TNF increases NO production (Kosaka et al, 1992) and causes NO-mediated vasodilatation and vascular hyporeactivity to vasoconstrictors in vivo (Vicaut & Baundry, 1992) and ex vivo (Takahashi et al, 1992;Foulkes & Shaw, 1992).…”
Section: Introductionmentioning
confidence: 99%